Lyric lais: volume II - Buckley, Ann (Newton Abbot Antico edition)
This second volume of thirteenth-century lyric lais contains three works in Latin, French and English: Flos pudicitie/Flur de virginité, a song to the Virgin; Lasse, que devendrai ge, a song on the Crucifixion; and Eyns ne soy ke plante/Ar ne kuth ich sorghe non, a prisoners lament